2017
DOI: 10.3389/fphar.2017.00482
|View full text |Cite
|
Sign up to set email alerts
|

Perilla frutescens Extracts Protects against Dextran Sulfate Sodium-Induced Murine Colitis: NF-κB, STAT3, and Nrf2 as Putative Targets

Abstract: Perilla frutescens is a culinary and medicinal herb which has a strong anti-inflammatory and antioxidative effects. In the present study, we investigated the effects of Perilla frutescens extract (PE) against dextran sulfate sodium (DSS)-induced mouse colitis, an animal model that mimics human inflammatory bowel disease (IBD). Five-week-old male ICR mice were treated with a daily dose of PE (20 or 100 mg/kg, p.o.) for 1 week, followed by administration of 3% DSS in double distilled drinking water and PE by gav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 44 publications
(44 reference statements)
2
22
0
Order By: Relevance
“…The functional interactions between NF-κB and STAT3 enhance inflammation in the intestinal mucosa and have been investigated in other studies [25,26]. In contrast, abrogation of NF-κB and STAT3 activation has been reported to be associated with improvements in intestinal homeostasis in DSS-administrated mice [27]. The present study showed that CEE administration potently attenuated the DSS-mediated increases in the phosphorylation levels of p65 and STAT3 in colonic tissues.…”
Section: Discussionsupporting
confidence: 45%
“…The functional interactions between NF-κB and STAT3 enhance inflammation in the intestinal mucosa and have been investigated in other studies [25,26]. In contrast, abrogation of NF-κB and STAT3 activation has been reported to be associated with improvements in intestinal homeostasis in DSS-administrated mice [27]. The present study showed that CEE administration potently attenuated the DSS-mediated increases in the phosphorylation levels of p65 and STAT3 in colonic tissues.…”
Section: Discussionsupporting
confidence: 45%
“…At present, an increasing number of researches ( Yang et al, 2016 ; Ahmed et al, 2017 ) have begun to focus on the role of Nrf2/Keap1 pathway in the inflammation-associated pathogenesis, as well as the suppression of pro-inflammatory signaling pathways. Besides, previous studies have demonstrated the decreased expression of Nrf2 in dextran sulfate sodium (DSS)-induced UC model and the important role of Nrf2 signaling pathway in UC treatment by some chemo-preventive agents ( Dae Park et al, 2017 ; Seo et al, 2017 ; Liu et al, 2018 ; Tan and Zheng, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…The DSS-induced colitis model mimics human inflammatory bowel disease appropriately ( 42 ); therefore, this model was used to investigate the effect of EEN on colitis. In the present study, EEN attenuated colitis injury and inflammatory symptoms induced by DSS, such as weight loss, shortening of colon length and colonic tissue damage.…”
Section: Discussionmentioning
confidence: 99%